Agroecology sustainable ecosystem - Anand M. R.; Kommireddy, Poojitha; Seenappa C.; Kalyana Murthy K. N.; Ningaraju G. K.; Elite Publishing House (Abingdon, Oxon, [England] CRC Press, an imprint of the Taylor & Francis Group, 2024)
Agroecology literacy is 'the degree to which people have an objective and well-informed understanding of crop production with environmental issues.' The increased food grain production has also increased the unscientific and indiscriminate use of agrochemicals which has affected the soil health and degraded agroecosystem adversely and brought down the immunity of soil and the productivity of crops. In addition, it has resulted in the over-exploitation of soil, leading to nutrient imbalance. Moreover, the negative impact of chemical agriculture on the environment and human health has been reported and documented. Increased environmental awareness and health consciousness promoted scientists and planners to think about sustainable farming practices as an alternate way for healthy agriculture to protect the environment and human health. Eco-friendly methods or ecosystem services are one solution to manage this issue. This book intends to provide the core elements of a curriculum for teaching agroecology at colleges and universities.--Provided by publisher.
1. Concept of Crop Ecology -- 2. Historical Developments -- 3. Levels in Ecological Organization -- 4. Crop Ecology -- 5. Plants Distribution and Adaptations -- 6. Agro-Climatic Zones of India -- 7. Ecosystem -- 8. Bio-Geochemical Cycles -- 9. Ecological Succession -- 10. Competition in Crop Plants -- 11. Environmental Pollution -- 12. Ecological Factors Affecting Crop Production -- 13. Ecology of Cropping System -- 14. Response of Crops To Light, Temperature and Co2 on Growth and Development -- 15. Ecological Basis for Environmental Management -- 16. Environmental Manipulation Through Agronomic Measures -- 17. Improvement of Unproductive Lands Through Crop Selection and Management -- 18. Effect of Climate Change on Crop Production -- 19. Exploitation of Solar Energy in Agriculture.
Includes bibliographical references.
Keywords: Agricultural ecology; Sustainable agriculture; Agricultural systems